PERAN SISTEM KEUANGAN DESA (SISKEUDES) DALAM PENGELOLAAN DANA DESA DI DESA CINGAMBUL KECAMATAN CINGAMBUL KABUPATEN MAJALENGKA - diding bajuri; ujang permana (Jurnal Ilmu Administrasi CENDEKIA, 2022)
ABSTRACTThis research is based on the existence of problems, namely in the Role of the Village Financial System (Siskeudes) in the Management of Village Funds in Cingambul Village, Cingambul District, Majalengka Regency, it is still not optimal and effective, based on observations of these symptoms, it is suspected that the implementation of the village financial system (Siskeudes) has not been fully implemented in accordance with the prevailing Regulation of the Minister of Home Affairs.Given these problems, the authors are interested in conducting research whose results will be set forth in the form of a thesis entitled